Digital breast tomosynthesis: Mean glandular dose estimation using monte carlo code. (September 2016) - Tzamicha, E.; Dimitriadis, A.; Gonis, H.; Georgiou, E.; Tsapaki, V.; Yakoumakis, N.; Yakoumakis, E.
Abstract : Introduction: 3D breast imaging using the technique of digital tomosynthesis may have the ability to improve the visualization of tissues which would be superimposed on a conventional mammogram. Early results with digital tomosynthesis are promising. Purpose: To estimate mean glandular dose (MGD) from tomosynthesis imaging of the breast using Monte Carlo code and voxel phantom in standing posture. Materials and methods: EGSnrc Monte Carlo code was used to simulate the interaction of photons with matter included a female voxel phantom (breast thickness of 2-8 cm and 50% glandular fraction). For the selection of X-ray spectrum, Automatic Exposure Control of Digital Breast Tomosynthesis was used. For each imaging condition were computed the glandular dose for the zero degree projection angle and the glandular dose for non-zero projection angles in 2° steps (scan range was −25° to +25°). The calculations were made for the X-ray spectra from a W target (tube voltage range 25–40 kV) filtered by Rh. Results: Acquisition of a cranio-caudal view resulted in an MGD ranging from 0, 318 to 2, 347 mGy. For a breast with a thickness of 5 cm and 50% glandular fraction, the MGD was 2.061 mGy. There is no significant difference between the MGD for CC and MLO mode. Conclusion: The results of this study are limited to providing the MGD to voxels phantoms of various thickness and only 50% glandular fraction. Future studies of the resulting dose from various glandular fractions are needed.